Rhizosphere Bacterial Communities Differ According to Fertilizer Regimes and Cabbage (Brassica oleracea var. capitata L.) Harvest Time, but Not Aphid Herbivory - O’Brien, Flora J. M.; Dumont, Marc G.; Webb, Jeremy S.; Poppy, Guy M. (Frontiers in Microbiology, 2018)
Rhizosphere microbial communities are known to be highly diverse and strongly dependent on various attributes of the host plant, such as species, nutritional status and growth stage. High-throughput 16S rRNA gene amplicon sequencing has been used to characterise the rhizosphere bacterial community of many important crop species, but this is the first study to date to characterise the bacterial and archaeal community of Brassica oleracea var. capitata. The study also tested the response of the bacterial community to fertiliser type (organic or synthetic) and N dosage (high or low), in addition to plant age (9 or 12 weeks) and aphid (Myzus persicae) herbivory (present/absent). The impact of aboveground herbivory on belowground microbial communities has received little attention in the literature, and since the type (organic or mineral) and amount of fertiliser applications are known to affect M. percicae populations, these treatments were applied at agricultural rates to test for synergistic effects on the soil bacterial community. Fertiliser type and plant growth were found to result in significantly different rhizosphere bacterial communities, whilst there was no effect of aphid herbivory. Several OTUs were identified as varying significantly in abundance between the treatment groups and age cohorts. These included members of the S-oxidising genus Thiobacillus which was significantly more abundant in organically fertilised 12-week old cabbages, and the N-fixing cyanobacteria Phormidium, which appeared to decline in synthetically fertilised soils relative to controls. These responses may be an effect of accumulating root-derived glucosinolates in the B. oleracea rhizosphere and increased N-availability respectively.